SISDIKNAS IN THE STUDY OF PANCASILA PHILOSOPHY AND THE STATE CONSTITUTION OF THE 1945 Constitution - Dasep Hanan Mubarok (Sean Institute, 2022)
That in fact independence is the right of all nations and because of that, colonialism in the world must be abolished, because it is not in accordance with humanity and justice. And the struggle for the Indonesian independence movement has come to a happy moment and safely delivered the Indonesian people to the front gate of the independence of the Indonesian State which is independent, united, sovereign, just and prosperous. By the grace of Allah the Almighty and with the encouragement of a noble desire to live a free national life, the Indonesian people hereby declare their independence. Then from that to form a Government of the State of Indonesia which protects the entire Indonesian nation and the entire homeland of Indonesia and to promote public welfare, educate the nation's life and participate in carrying out world order based on independence, eternal peace and social justice, the Indonesian National Independence was drafted. in a Constitution of the State of Indonesia, which is formed in a structure of the Republic of Indonesia, which has sovereignty of the people based on: Belief in One Supreme God, just and civilized humanity, Indonesian Unity, Democracy led by wisdom in deliberation/representation, and realizing social justice for all Indonesian people. In Law Number 20 of 2003 concerning the National Education System, the implementation of education must adhere to several principles, namely education is carried out in a democratic and fair manner and is not discriminatory by upholding human rights, religious values, cultural values, and national pluralism with a systemic unity with open and multi-meaning system. In addition, it must be in a process of cultivating and empowering students that lasts a lifetime by setting an example, building the will, and developing the creativity of students in the learning process through developing a culture of reading, writing, and arithmetic for all community members, empowering all components of society through the role of as well as in the implementation and control of the quality of education services. Researchers use research methods based on literature studies through literature reviews in order to obtain a factual and clear description and analysis of the objectives of the National Education System (Sisdiknas) which is based on the Pancasila philosophy and the 1945 constitution of the state, because the Pancasila philosophy is the source of all sources of law. within the Unitary State of the Republic of Indonesia.